Biodiversity Among Brettanomyces Bruxellensis Strains Isolated from Different Wine Regions of Chile: Key Factors Revealed About Its Tolerance to Sulphite - Ganga-Munoz, M; González-Poblete, C (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
Brettanomyces bruxellensis is regarded as the main spoilage microorganism in the wine industry, owing to its production of off-flavours. It is difficult to eradicate owing to its high tolerance of adverse environmental conditions, such as low nutrient availability, low pH, and high levels of ethanol and SO2. In this study, the production of volatile phenols and the growth kinetics of isolates from various regions of Chile were evaluated under stressful conditions. Through randomly amplified polymorphic DNA (RAPD) analysis, 15 strains were identified. These were grown in the presence of p-coumaric acid, a natural antimicrobial and the main precursor of off-flavours, and molecular sulfur dioxide (mSO2), an antimicrobial synthetic used in the wine industry. When both compounds were used simultaneously, there were clear signs of an improvement in the fitness of most of the isolates, which showed an antagonistic interaction in which p-coumaric acid mitigates the effects of SO2. Fourteen strains were able to produce 4-vinylphenol, which showed signs of phenylacrylic acid decarboxylase activity, and most of them produced 4-ethylphenol as a result of active vinylphenol reductase. These results demonstrate for the first time the serious implications of using p-coumaric acid, not only for the production of off-flavours, but also for its protective action against the toxic effects of SO2. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.